BCA Syariah VS BCA Konvensional: Analisis Rasio BOPO dan ROA - Yulfiswandi Yulfiswandi; Delfina Delfina; Fionna Quinn; Alexander J. W; Rudiyanto Rudiyanto; Hardy W. L (Pascasarjana STIE Amkop Makassar, 2022)
AbstrakThis study was done to analyze the performance of the two types of banks along with the quick development of Islamic banks as they entered the market and started to compete with conventional banks. The ratios of two PT Bank Central Asia Tbk subsidiaries, conventional BCA and syariah BCA, which operate under distinct operating principles, are compared in this study using a comparative technique. The annual report of BCA provides information on financial ratios for the years 2018 through 2021 where ROA and BOPO ratios are used as research variables in this report. The results showed that there were visible differences in the BOPO ratio of syariah BCA and conventional BCA. BCA syariah BOPO ratios vary from 84% to 88%, while conventional BCA BOPO ratios range from 53% to 60% for the 2018-2021 period. The efficiency of syariah and conventional BCA will also improve in 2021, as shown by a decrease in the BOPO ratio from the previous year, followed by an increase in ROA due to net profit growth.Â Kata Kunci: BOPO, Conventional BCA, Syariah BCA, ROA